Association of Lower Serum Bilirubin With Loss of Residual Kidney Function in Peritoneal Dialysis Patients. Issue 2 (25th July 2019) - Tsujikawa, Hiroaki; Tanaka, Shigeru; Hara, Masatoshi; Kawai, Yasuhiro; Matsukuma, Yuta; Torisu, Kumiko; Nakano, Toshiaki; Tsuruya, Kazuhiko; Kitazono, Takanari
Abstract: Bilirubin is recognized as an endogenous antioxidant, and low serum bilirubin is reported to be associated with the progression of kidney disease. However, it is unclear whether serum bilirubin levels are associated with the loss of residual kidney function (RKF) in peritoneal dialysis (PD) patients. This study investigated the relationship between serum total bilirubin and loss of RKF. We prospectively followed 94 PD patients who started PD in our hospital between June 2006 and May 2016. Ten patients who had chronic liver disease or cirrhosis were excluded. Patients were divided into three groups based on serum total bilirubin concentration tertiles: tertile 1 ( T 1) < 0.3, T 2 = 0.3, and T 3 ≥ 0.4 mg/dL. We estimated the relationship between serum bilirubin and loss of RKF, defined as daily urine volume (<100 mL) within 3 years after starting PD, using a Cox proportional hazards model. During the 3‐year observation period, 22 patients lost RKF. The incidence rate of loss of RKF increased linearly with the decrease in serum total bilirubin levels ( P for trend < 0.05). After adjusting for confounding factors, low serum total bilirubin level was shown to be an independent predictor of loss of RKF (hazard ratio [HR] for every 0.1 mg/dL decrease, 1.50; 95% confidence interval [CI], 1.01–2.51; HR [95%CI] for T2 and T1 [vs. T3] 2.03 [0.65–7.88] and 3.70 [1.00–15.9]). This study suggests that low serum total bilirubin levels are associated with the loss of RKF in PD patients.